Investigation of radiated emissions of a galvanically isolated qZS DC-DC converter; 5th IEEE International Conference on Power Engineering, Energy and Electrical Drives: POWERENG, Riga, May 11-13, 2015 - Jalakas T. Tanel; Jarkovoi J. Marek; Roasto I. Indrek; Zakis J. Janis; Garganeev A. G. Alexander Georgievich (2015, 2015)
Title screen